2021
DOI: 10.1177/17455065211055304
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of undergraduate healthcare student perspectives regarding human papillomavirus and vaccine intent in India

Abstract: Objective: Safe and effective human papillomavirus vaccines are available against cervical cancer and other human papillomavirus–associated diseases. Vaccine uptake is low in India given lack of universal vaccination programme. This exploratory study describes the medical, dental and nursing undergraduate student perspectives about human papillomavirus and intentions to receive the vaccine. Methods: Using a cross-sectional, explorative study design, we conducted two focus group discussions among a convenience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…It was no wonder that medical students would have higher awareness rates toward HPV due to the information they receive as a part of their education. This finding is consistent with other studies from India and Malaysia [20,41], which indicated a higher level of HPV awareness among medical students compared to nursing students. A similar study on medical and nursing students in Turkey also showed that nursing students have lower-level knowledge of HPV [42].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was no wonder that medical students would have higher awareness rates toward HPV due to the information they receive as a part of their education. This finding is consistent with other studies from India and Malaysia [20,41], which indicated a higher level of HPV awareness among medical students compared to nursing students. A similar study on medical and nursing students in Turkey also showed that nursing students have lower-level knowledge of HPV [42].…”
Section: Discussionsupporting
confidence: 93%
“…The finding of this study indicated that most than half of the study participants had good awareness/knowledge about the HPV infection and its vaccine. This finding is consistent with the studies conducted in Iran [17,18], Iraq [19] and India [20]. However, this finding is higher than the studies done in Malaysia [21] and Turkey [22].…”
Section: Discussionsupporting
confidence: 91%
“…Out of these 7 studies, two included both female and male participants. Both studies were university-based studies and the participants were undergraduate healthcare students ( 39 , 40 ). The geographical location of the studies varied, with 2 of them taking place in rural areas and 2 in universities in Mangalore ( Figure 2 ) ( 39 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies targeting healthcare students in Mangalore by Padmanabha et al and by Shetty et. al reported the use of audio-visual presentations lasting from 5 to 20 min ( 39 , 40 ). In a study by Ramavath & Olyai targeting adolescent girls in schools and colleges across urban India, the researchers provided lectures focusing on health ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation